Differentiation Strategy of Soes Construction Service in Indonesia: A Point of View of Project Managers - Siregar, Siddik; Irsan Siregar, Eddy; ., . (International Journal of Engineering and Technology, 2018)
This research is an empirical study on State-Owned Enterprises [SOEs] Construction Service in Indonesia. The main objective of this study is to analyze the variables concerning the performance of innovation management and information & communication technology [ICT]. The study population is managers and decision makers on large-scale SOEs Construction Service in Indonesia. Respondents in this study are nine SOEs on Construction Service and the people involved in the construction service business with a total of 102 people. The respondents' answers are developed from theoretical framework and processed using confirmatory analysis of SEM [Structural Equation Modeling] that processed by SPSS AMOS 22 Program. The research results show that: [1] Innovation Management affects Differentiation Strategy significantly. [2] Innovation Management affects Company Performance. [3] Information and Communication Technology affects Differentiation Strategy significantly. [4] Information & Communication Technology affects Company Performance but insignificance. [5] Differentiation Strategy affects Company Performance significantly.Â Â